BIOCODICOLOGY: UNVEILING THE BIOLOGICAL AND MATERIAL COMPOSITION OF ANCIENT MANUSCRIPTS - Sabri, Mansour Mohamed (Journal of Natural Sciences and Learning, 2024)
Biocodicology is an emerging interdisciplinary field that integrates biology, archaeology, and information science to study ancient manuscripts. This paper explores how biological analysis, including DNA and protein analysis, combined with advanced imaging techniques such as Reflectance Transformation Imaging (RTI), Multispectral Imaging (MSI), X-ray Fluorescence (XRF), and Fourier Transform Infrared (FTIR) Spectroscopy, offers new insights into the origins, production, and preservation of historical manuscripts. DNA extraction and protein analysis reveal the biological origins of the materials, while non-invasive physicochemical methods uncover the chemical composition of inks and pigments. The integration of bioinformatics and machine learning tools provides a holistic understanding of manuscript production techniques and environmental conditions. These methodologies contribute significantly to the study of historical manuscripts and inform strategies for their conservation and preservation.